Sub chronic toxicity effect of combination of herbal juice on the function and 2 histopathology feature of male Wistar rat liver - Ade Arinia Rasyad; Aisah Aisah; Lidia Lidia; Sari Meisyayati (Jurnal Ilmiah Farmasi, 2022)
Abstract Background: Previously, the activity test of the combination herbal juice of garlic, rosella flower, red ginger, lime, apple cider vinegar, and honey, combined herbal juice can lower blood sugar [1] and can reduce total cholesterol levels [11]. In the use of traditional medicine and its effectiveness, its safety must also be proven before herbal juices are circulated in the communityObjective: This study was to determine the subacute hepatotoxic effect of the combination herbal juiceMethod: This research is an experimental study using 24 rats divided into four groups. Namely, the control group was given distilled water, and the group was given the combination herbal juice at a dose of 28, 14, and 7 mg/kg BW/day for 28 days. The measurement parameters were the increased activity of SGOT and SGPT and histopathological features of liver cells. The data were statistically analyzed with one-way ANOVA analysisResults: The administration of combination herbal juice for 28 days at a dose of 28, 14, and 7 mg/kg BW/day did not increase SGOT activity but caused a significant decrease in SGPT levels, namely by 20.34%, 19.39%, and 15.30%. From the histopathological picture of liver cells, at a dose of 28 mg/kg BW/day, there was no histopathological damage to liver cellsConclusion: Subacute administration of combined herbal juice did not cause hepatotoxicity in Wistar male white ratsKeywords: Combination herbal juice, subacute toxicity, histopathology, SGOT, and SGPT Intisari Latar belakang: Telah dilakukan sebelumnya uji aktivitas dari jus herbal kombinasi bawang putih, bunga rosella, jahe merah, jeruk nipis cuka apel dan madu,  jus herbal kombinasi dapat menurunkan gula darah  [1] dan dapat menurunkan kadar kolesterol total [11]. Dalam penggunaan obat tradisional, selain efektifitasnya, keamanannya pun harus dibuktikan sebelum jus herbal beredar dimasyarakatTujuan: Penelitian ini untuk mengetahui efek hepatotoksik sub akut dari jus herbal kombinasiMetode: Penelitian ini bersifat eksperimental menggunakan 24 ekor tikus yang terbagi dalam 4 kelompok. yaitu kelompok kontrol yang diberi akuades dan kelompok yang diberi jus herbal kombinasi dengan dosis 28, 14 dan 7 mg/kgBB/hari selama 28 hari. Parameter pengukuran adalah peningkatan aktivitas SGOT dan SGPT serta gambaran histopatologi sel hati. Data dianalisa secara statistik dengan  analisa ANOVA satu arahHasil: Pemberian jus herbal kombinasi selama 28 hari dengan dosis 28, 14 dan 7 mg/kgBB/hari tidak menyebabkan peningkatan aktifitas SGOT  tetapi menyebabkan penurunan kadar SGPT secara signifikan yaitu sebesar 20,34 %, 19,39 % dan 15,30 %. Dari gambaran histopatologi sel  hati, dosis 28 mg/kggBB/hari tidak ditemukan kerusakan histopatologi sel hatiKesimpulan: Pemberian subakut jus herbal kombinasi tidak menyebabkan hepatotoksik pada  tikus putih jantan galur wistarKata kunci : Jus herbal kombinasi, toksisitas subakut, histopatologi, SGOT, dan SGPT